2008
DOI: 10.1007/s12275-007-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterization of human enteroviruses in Korean surface water

Abstract: In this study, the genetic epidemiology of enteroviruses (EVs) in Korean surface water was evaluated by conducting phylogenetic analyses of the nucleotide sequences of the 5' non-coding region (5' NCR), which was determined by RT-PCR analysis of total culturable virus assay-positive samples. The results showed that the nucleotide sequences of the EVs could be classified into 4 genetic clusters, and that the predominant presence of Korea EVs were very similar to echoviruses type 30. Interestingly, two nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…genotype IA HAVs isolated from Korean patients. These findings are concordant with previous reports that enteroviruses found in patients are also present in water environments (26,57), and suggest transmission of HAVs from patients to water environments in Korea. Lee et al (18) and Yun et al (28) have reported several amino acid substitutions in the VP3/VP1 junction region of HAVs detected in Korea.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…genotype IA HAVs isolated from Korean patients. These findings are concordant with previous reports that enteroviruses found in patients are also present in water environments (26,57), and suggest transmission of HAVs from patients to water environments in Korea. Lee et al (18) and Yun et al (28) have reported several amino acid substitutions in the VP3/VP1 junction region of HAVs detected in Korea.…”
Section: Discussionsupporting
confidence: 93%
“…The genetic sequences of the genotype IA HAVs detected in this study clustered closely with those of genotype IA HAVs isolated from Korean patients. These findings are concordant with previous reports that enteroviruses found in patients are also present in water environments , and suggest transmission of HAVs from patients to water environments in Korea.…”
Section: Discussionsupporting
confidence: 92%
“…The first cultures were thawed and filtered with 0.22 µm sterilizing filters. The filtered cultures (1 mL) were inoculated and cultured for 14 days, as previously described (18,19). Samples that exhibited CPE in both the first and second cultures were considered c 2012 The Societies and Wiley Publishing Asia Pty Ltd EV-positive.…”
Section: Total Culturable Virus Assaymentioning
confidence: 99%
“…Lee and Lee [12] demonstrated that the prevalence and density of enteroviruses were low in most water sources. However, in groundwater, it was demonstrated that the NoV occurrence was 21.7% in the summer and 17.3% in the winter [17].…”
Section: Discussionmentioning
confidence: 99%
“…1). The viruses were sampled and concentrated following the United States Environmental Protection Agency (USEPA) guidelines [23], as previously described [12]. In brief, 200 L of raw water was collected in a device that included a flow meter, a pressure gauge, a cartridge containing a 1MDS positively charged filter (CUNO, Meriden, CT, USA), and tubing.…”
Section: Samplingmentioning
confidence: 99%